Analisis Faktor yang Mempengaruhi Minat Masyarakat Muslim dalam Berwakaf Uang di Kota Medan - Sakina, Shania; Yenni Samri Juliati Nasution; Nurul Inayah (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
In Islam there are several forms of institutions that are expected to be able to support socio-economic welfare, one of which is waqf. Waqf is holding property that can be taken advantage of without being destroyed and for permissible use (not prohibited by syara) and is intended to gain the pleasure of Allah SWT. So far, people only know waqf in the form of land and buildings. While waqf in the form of money has not been well socialized. The lack of public understanding and knowledge about cash waqf has resulted in fewer people participating in cash waqf. The purpose of this study was to determine and analyze the influence of attitudes, religiosity and information media on the interest of the Muslim community in cash waqf in the city of Medan. The quantitative research method uses primary data by distributing questionnaires to the Muslim community in the city of Medan, totaling 100 samples. The results of the study can be seen from the R Square value of 57% which means that attitudes, religiosity and information media have an effect of 57% on the interest in cash waqf in the city of Medan, while 43% is influenced by other variables not discussed in this study.